Chile’s Solidarity Pillar : A Benchmark for Adjoining Zero Pillar with DC Schemes - Fajnzylber, Eduardo (World Bank, Washington, DC, 2019)
In 2008, Chile introduced a New Solidarity Pillar (NSP) designed to eliminate the incidence of poverty among elderly adults by setting a floor at around forty percent of the minimum monthly income for the poorest sixty percent of the population. This paper describes the NSP’s main characteristics and the main results achieved during its first seven years of operations: coverage, fiscal cost, poverty reduction, and the system’s role in reducing the significant gender gap in pensions. Its effects on incentives to contribute are discussed, as well as the literature that has attempted to measure these effects. Finally, the main challenges facing the NSP and the implications for other countries under defined contribution pension schemes are summarized.